Pyrolysis and gasification integrated process of empty fruit bunch for multi-biofuels production: Technical and economic analyses. (15th April 2022) - Detchusananard, Thanaphorn; Wuttipisan, Natnapong; Limleamthong, Phantisa; Prasertcharoensuk, Phuet; Maréchal, François; Arpornwichanop, Amornchai
Highlights: Pyrolysis and gasification integrated process of empty fruit bunch for multi-biofuels production was investigated. Process and economic analyses were performed to find optimal conditions and evaluate the process feasibility. The integrated process was economically feasible and attractive with 5.98 years of PB and 22% of IRR. Abstract: The use of renewable energy sources has been promoted with concern about limited fossil fuels and increased environmental impact. Empty fruit bunch (EFB), which is a valuable biomass residual from palm oil milling processes, is one of the most promising renewable energy sources that can be used to increase the monetary value of EFB through the pyrolysis and gasification integrated process for multi-biofuels production. This work aims to perform technical and economic analyses of the pyrolysis and gasification integrated process using EFB for multi-biofuels production. Firstly, the pyrolysis and gasification integrated process model is developed by using Aspen Plus simulator and employed to determine optimal conditions through a parametric analysis. Then, the design of a heat exchanger network is also incorporated to enhance the energy efficiency of the process using Aspen Energy Analyzer. Finally, the key economic performance indicators, i.e., payback period (PB), net present value (NPV), and internal rate of return (IRR), of the process are analyzed using Aspen Process Economic Analyzer. The results show that the integrated process should be operated at steam to biochar mass ratio of 2.7, gasifier temperature of 900 °C, steam to syngas mass ratio of 3.0, and WGS temperature of 240 °C to produce the maximum hydrogen, gases, gasoline, naphtha, kerosene and diesel at 140, 290, 657, 729, 298 and 811 kg h −1, respectively. Furthermore, in terms of heat integration, the minimum hot and cold utilities are required at 21, 554 and 5, 247 MJ h −1, respectively. The economic analysis results indicate that the proposed process is economically feasible and attractive with 5.98 years of PB, 249, 951, 964 of NPV, and 22% of IRR.